Surface modification effects on nanocellulose – molecular dynamics simulations using umbrella sampling and computational alchemy. Issue 44 (9th November 2020) - Chen, Pan; Lo Re, Giada; Berglund, Lars A.; Wohlert, Jakob
Abstract : Topochemical modification of nanocellulose particles, in particular acetylation, is commonly used to reduce hygroscopicity and improve their dispersibility in non-polar polymers. Abstract : Topochemical modification of nanocellulose particles, in particular acetylation, is commonly used to reduce hygroscopicity and improve their dispersibility in non-polar polymers. Despite enormous experimental efforts on cellulose surface modification, there is currently no comprehensive model which considers both (a) the specific interactions between nanocellulose particles and the surrounding liquid or polymer matrix, and (b) the interactions between the particles themselves. The second mechanism is therefore frequently ignored. The present approach is based on atomistic molecular dynamics (MD) simulations, where computational alchemy is used to calculate the changes in interactions between nanocellulose and the surrounding medium (liquid or polymer) upon modification. This is combined with another method, based on potential of mean force, to calculate interactions between particles. Results show that both contributions are of equal importance for nanoparticle surface acetylation effects. The proposed method is not restricted to either cellulose or acetylation, and has the prospect to find application in a broad context of nanomaterials design.